Temperature and Growth: A Panel Analysis of the United States - Riccardo Colacito; Bridget Hoffmann; Toan Phan (Inter-American Development Bank (IDB), 2016)
This paper documents that seasonal temperatures have significant and systematic effects on the U.S. economy, both at the aggregate level and across a wide crosssection of economic sectors. This effect is particularly strong for the summer: an increase of 1êF in the average summer temperature is associated with a reduction in the annual growth rate of state-level output of 0:15 to 0:25 percentage points. When these estimates are combined with projected increases in seasonal temperatures it is found that a reduction of U.S. economic growth by up to one third could occur over the next century.
hdl:11319/7654
Keywords: O44; Q51; Q59; R11; 330; Climate change; Growth